INVESTIGATING DIGITAL SHARED READING FOR VOCABULARY AND READING COMPREHENSION IN PRIMARY EFL LEARNERS - Oktaviani, Putri; Anita, Anita; Fitriani, Dini (Universitas Tanjungpura, 2026)
This study aims to describe the implementation of digital shared reading in primary school, analyze its influence on students' vocabulary mastery and reading comprehension, and identify supporting and inhibiting factors in its implementation. A qualitative descriptive methods was employed, with data collected through observation, interviews, and document analysis (teaching modules, teaching materials, and digital media). Participants consisted of one English teacher and 4th-grade primary school students. The qualitative data were systematically coded and analyzed using NVivo 14 to identify emerging themes and patterns. The results showed that digital shared reading implemented in a structured, interactive, and adaptive manner enhances students’ cognitive and affective engagement. The integration of text, images, and audio narration in digital storybooks helps students understand meaning contextually and strengthens their memory of new vocabulary. However, the barriers include limited digital infrastructure, short learning durations, and a lack of digital reading materials that represent local culture